Pernikahan Dini; Ditinjau dari Aspek Psikologi - Surawan Surawan (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2019)
Marriage is something sacred, for that it needs careful preparation both physically, economically and psychologically. For this reason, the aims of this study are 1) the causes of early marriage, 2) the psychological impact of early marriage and 3) the strategy to overcome the negative effects of early marriage in Sanden District, Bantul Regency in 2015-2018. This research used qualitative descriptive method which was carried out in Sanden District, Bantul Regency in 2015-2018. The research was carried out in January-March 2018 involved 10 respondents’ early marriage partners. Data collection techniques used interview, observation and documentation. Whereas data analysis used data reduction, display and data verification or conclusions. The results of this study were 1) the causes of early marriage were a) due to pregnancy before marriage and b) parental factors (economic, education, parenting parents and the level of understanding of parents' religion). Whereas 2) the psychological impact of early marriage was a) disruption of adjustment, b) family harmonization, c) theincrease of divorce rate, d) disrupted of social relations, e) parenting towards children who were not continuous, f) education was stalled and g) economic downturn. For 3) strategies for overcoming the negative effects of early marriage were a) cooperation between families and religious affair office (KUA) counselors by communicating intensely with children, always provided motivation and provided positive role models for children. b) local governments (villages, health center and KUA instructors) by provided advice or counseling on the dangers of association and reproduction, data collection of people who were going to get married, provided socialization to villages, schools by cooperated with KUA and health center, and tightened the law on marriage.